2020
DOI: 10.1039/d0ob01890b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and oligomerization of cysteinyl nucleosides

Abstract: Nucleoside and nucleic acid analogues are known to possess a considerable therapeutic potential. In this work, by coupling cysteine to nucleosides, we successfully synthesized compounds that may not only have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Thus, if the conversion was not satisfactory after 15 min., the reaction mixture was subjected to UV-irradiation for further 1-2 × 15 min. The thiol-ene coupling is tolerant to water and oxygen and is compatible with any solvent [24,[31][32][33]. Therefore, we performed the reactions without any caution to exclude air or moisture, and selected different solvents on the basis of the solubility of the reactants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, if the conversion was not satisfactory after 15 min., the reaction mixture was subjected to UV-irradiation for further 1-2 × 15 min. The thiol-ene coupling is tolerant to water and oxygen and is compatible with any solvent [24,[31][32][33]. Therefore, we performed the reactions without any caution to exclude air or moisture, and selected different solvents on the basis of the solubility of the reactants.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have demonstrated that the reaction temperature influences the efficacy of the photoinitiated thiol-ene reactions in a unique way. Cooling promotes, whereas heating inhibits, the thiol-ene couplings [20][21][22]24,[31][32][33].…”
Section: Resultsmentioning
confidence: 99%
“…We have also shown, that the thiol-ene coupling reaction of C4'-exomethylene derivatives of nucleosides provides an easy route to 5'-thioconjugated derivatives. [16,17] On the basis of these results we envisioned the replacement of the pyrophosphate unit of UDP-sugars with a dithio-alkyl group by two subsequent thiol-ene coupling reactions using 1,2-ethanedithiol II as the thiol and glycals I and nucleosides III as the alkene reactants (Scheme 1B). Moreover, the thiol-ene coupling reaction was also exploited for the synthesis of morpholine ring nucleoside analogues as potential GT inhibitors via hydrothiolation of 2-substituted glycals I with thioacetic acid IV and coupling of the ensuing α-thiols to N-allyl morpholinos V (Scheme 1C).…”
mentioning
confidence: 99%
“…[15,16] We have demonstrated that hydrothioylation of C4'-exomethylene derivatives of nucleosides at room temperature proceeds with low stereoselectivity, but the level of stereoselectivity can be gradually increased by decreasing the reaction temperature. [16,17] Therefore, it was crucial to conduct the hydrothiolation of 4 at À 80 °C to achieve high D-ribo selectivity. The synthesis of compound 5 was also accomplished by first coupling 1,2-ethanedithiol monoacetate to uridine 4 and then reacting the resulting 6 a, [16] after selective S-deacetylation, with the glycal derivative 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation